ANALYSIS OF STUDENT MATHEMATIC COMMUNICATION DIFFICULTIES IN THE APPLICATION OF THE THINK PAIR SHARE LEARNING MODEL - Maryetta Evi Hariati; Bornok Sinaga; Mukhtar - (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2022)
This study aims to describe: (1) students' mathematical communication skills in the application of the Think Pair Share cooperative learning model; and (2) the difficulty of mathematical communication and students' creative thinking in solving mathematical problems through the Think Pair Share cooperative learning model. This research is a qualitative research with a descriptive approach. The subjects in this study involved 35 students of grade VII-1 SMP Wiraswasta Batangkuis for the academic year 2020/2021. Based on the research data, it was found that: (1) The level of students' mathematical communication skills on the material of rectangles and squares in medium-ability students had the highest proportion, followed by low and high-ability students; and (2) The difficulty of students' mathematical communication skills in applying the Think Pair Share learning model is the difficulty of facts, concepts, operations, and principles